Laugh your Rabbids off! : A Rabbids Joke book - McCarthy, Rebecca; Illustrated by Ruiz, Fernando (New York Simon & Schuster Children's Publishing, 2014)
The Rabbids are invading the Earth and bringing the funny with them in this joke book.
Include Illustrations
Keywords: Wit and humor, Juvenile